Pengoprasian Gmdss di Kapal KN. Karimun Jawa dalam Menunjang Keselamatan Bernavigasi - Iwan Mahendro; Reshandio Ramadhan (JURNAL BARTEK, 2025)
The world of maritime transportation is very prone to accidents, whether caused by human factors or technical errors in transportation equipment. In the shipping world, GMDSS equipment is a system that must be owned by commercial vessels. One of the problems related to GMDSS is that many do not understand and master the operation of GMDSS properly, so it has the potential for problems. The purpose of this study is to understand the operation of GMDSS in order to reduce the potential for disasters at sea. The function and role of (GMDSS) in an emergency/disaster at sea is to increase safety or minimize the occurrence of casualties and facilitate rescue efforts for ships, if an accident or emergency occurs at sea. The methods used in this study are observation, interviews, and documentation. The conclusion of this study is that GMDSS ensures the merchant ship KN. Karimun Jawa to be able to communicate well in emergency situations. This system helps ships to immediately report emergency conditions to the authorities, speeding up responses, and saving lives.